Challenges Faced by Emergency Physicians in China: An Observation From the Perspective of Burnout - Yan, Shijiao; Shen, Xin; Wang, Rixing; Luo, Zhiqian; Han, Xiaotong; Gan, Yong; Lv, Chuanzhu (Frontiers in Psychiatry, 2021)
Background: Burnout is considered a global problem, particularly in the emergency health sector; however, no large-sample cross-sectional study has assessed the prevalence of burnout among emergency physicians and its associated factors. Methods: A nationally representative cross-sectional survey of 15,243 emergency physicians was conducted in 31 provinces across China between July and September 2019. Multiple linear regression analysis was performed to identify correlates of burnout. Results: The participants' mean scores were 25.8 (SD = 15.9) on the emotional exhaustion (EE) subscale, 8.1 (SD = 7.9) on the depersonalization (DP) subscale, and 26.80 (SD = 12.5) on the personal accomplishment (PA) subscale, indicating a pattern of moderate EE, moderate DP, and high PA. The results of the large-sample survey found that 14.9% of emergency physicians had a high level of burnout in China, with 46.8% scoring high for EE, 24.1% scoring high for DP, and 60.5% having a high risk of low PA. Having poor self-perceived health status and sleep quality, working in developed regions and governmental hospitals, having an intermediate professional title, experiencing depression, performing shift work and experiencing workplace violence made emergency physicians more likely to experience occupational burnout. Conclusion: Positive measures should be taken to reduce the burnout of emergency physicians and improve their work enthusiasm to maintain the quality of emergency medical services.